OMEGA-3 FATTY ACIDS AND CARDIOVASCULAR DISEASE: A DECADE OF EVIDENCE - Maria Janiszewska; Agata Juchniewicz; Jakub Sapikowski; Iga Kuba; Julita Jagodzińska; Anna Lubomska; Martyna Grześkowiak; Jakub Idziński (International Journal of Innovative Technologies in Social Science, 2025)
Cardiovascular diseases (CVDs) remain the leading cause of morbidity and mortality worldwide. Omega-3 polyunsaturated fatty acids (PUFAs), particularly eicosapentaenoic acid EPA) and docosahexaenoic acid (DHA), have been proposed as cardioprotective agents through anti-inflammatory, antithrombotic, and plaque- stabilizing mechanisms. This review synthesizes evidence from randomized controlled trials (RCTs) and meta- analyses over the past decade, examining the effects of omega-3 supplementation on cardiovascular outcomes. High-dose purified EPA (4g/day icosapent ethyl) consistently reduces major adverse cardiovascular events (MACE) in high-risk populations [1,2]. Conversely, low-dose or mixed EPA+DHA formulations show variable or neutral results [3,4]. Mechanistic, biomarker, and imaging studies support biological plausibility of benefit [5], while safety signals- particularly increased risk of atrial fibrillation- should be considered [2,6]. Formulation, dosing, and patient selection are critical for optimizing cardiovascular outcomes.